Analisis Pesan Akhlak Di Akun Youtube @Channelfksmmsunggal - Fadlan Habib; Khatibah Khatibah (STAI Bumi Silampari, 2025)
This study aims to analyze the messages of da'wah contained within the YouTube channel @ChannelFKSMMSunggal by examining the community's interactions regarding the videos presented on the channel. The research employs a qualitative methodology with a descriptive approach. The object of the study is the YouTube channel @ChannelFKSMMSunggal, and data collection is conducted through observation, note-taking, and content analysis to determine whether the content already incorporates elements of da'wah, such as fiqh, aqeedah, and general Islamic studies. The applied analytical method is content analysis, which involves describing message characteristics by elaborating on the content, target audience, and form of the messages, ultimately leading to conclusions about the content’s messaging. It can be concluded that the @ChannelFKSMMSunggal YouTube channel presents Islamic materials that encompass the history of the prophets, aqeedah, fiqh, and discussions related to significant events and current phenomena, all grounded in the Qur'an and Hadith. This presentation links religious teachings with real-life phenomena and the stories of the prophets to reinforce the da'wah messages.